Long-term outcome after flexible ureteroscopy with holmium laser for simultaneous treatment of a single renal cyst and ipsilateral renal stones. Issue 8 (August 2019) - Zewu, Zhu; Hequn, Chen; Yu, Cui; Yang, Li; Zhongqing, Yang; Zhiyong, Chen; Feng, Zeng
Objective: To assess the long-term outcome of simultaneous treatment of a single renal cyst and ipsilateral stones with transurethral flexible ureteroscopy (FURS) lithotripsy and internal cyst drainage. Methods: Patients who underwent simultaneous treatment with FURS lithotripsy and internal cyst drainage in our institution between July 2014 and September 2017 were enrolled. The cyst wall was identified endoscopically and a 1–3-cm window was created in the wall using a holmium laser. The proximal end of a double-J stent was placed in the cystic cavity to facilitate internal drainage. Results: Thirteen patients underwent simultaneous treatment. No intraoperative complications with Clavien grading score >2 were noted in any patients. Mean stone burden and cyst diameter were 1.6 (range: 0.9–2.5) cm and 5.8 (range: 3.0–7.1) cm, respectively. Stone-free rates after single and complementary procedures were 84.6% and 92.3%, respectively. During the mean 33.1-month follow-up period (range: 17–54 months), seven patients (53.8%) achieved full resolution of renal cysts, five patients (38.5%) maintained >50% size reduction, and one patient (7.6%) experienced recurrence at 18 months postoperatively. Conclusions: FURS with a holmium laser may constitute a safe and effective alternative procedure for simultaneous treatment of a single renal cyst and ipsilateral stones.